2019
DOI: 10.1111/and.13442
|View full text |Cite
|
Sign up to set email alerts
|

Effects ofAnthocleista djalonensisroot extracts on reproductive hormones and testicular marker enzymes in adult male Wistar rats

Abstract: | INTRODUC TI ONMale fertility is controlled by a complex assortment of pituitarygonadal hormones and steroidogenic enzymes, and each of these enzymes works synergistically to maintain the proper function of the testis. The endocrine regulation of spermatogenesis is complex and consists of response mechanism involving hormones from hypothalamus, anterior pituitary gland and the reproductive organ (Wahab, Mokhtar, Halim, & Das, 2010). The gonadotropin-releasing hormone (GnRH), which is synthesised and discharge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…However, Ngwoke et al (2018) were investigated the DPPH scavenging ability of various extracts from stem barks of Anthocleista nobilis and the best ability was found in the ethyl acetate with the lowest IC 50 (220 µg/ mL). In the study of Ezirim et al (2019), phytochemical analysis of root extracts of A. djalonensis also showed that phenol and flavonoid constituents were higher in the methanol than in the aqueous ethanol extract and also had higher antioxidant activity. Therefore, this is in agreement with the findings obtained herein, showing methanol to be a better solvent to yield higher phytochemical content and antioxidant potential.…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…However, Ngwoke et al (2018) were investigated the DPPH scavenging ability of various extracts from stem barks of Anthocleista nobilis and the best ability was found in the ethyl acetate with the lowest IC 50 (220 µg/ mL). In the study of Ezirim et al (2019), phytochemical analysis of root extracts of A. djalonensis also showed that phenol and flavonoid constituents were higher in the methanol than in the aqueous ethanol extract and also had higher antioxidant activity. Therefore, this is in agreement with the findings obtained herein, showing methanol to be a better solvent to yield higher phytochemical content and antioxidant potential.…”
Section: Antioxidant Capacitymentioning
confidence: 98%
“…Traditionally, these parts are prepared as decoctions or macerations using culturally accepted and available solvents like local gin or hot/boiling water and administered orally. Previous studies have shown that different parts of Anthocleista djalonensis may have useful medical properties, such as antidiabetic, antimalarial, antipyretic, anthelmintic, antimycobacterial, antibacterial, and wound healing properties [3,4,5]. These medicinal properties of Anthocleista djalonensis makes its worthy to be explored for both traditional and modern medical benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Anthocleista djalonensis (A. djalonensis), commonly known as the cabbage tree, belongs to the Gentianaceae family, is widely found in the tropical rainforests of West Africa [1], and stands out for its acknowledged traditional usage in herbal medicine in Nigeria. Various parts of this plant have been shown in scientific reports to have anti-inflammatory, antidiabetic, analgesic, antifungal, and antimalarial properties [2][3][4].…”
Section: Introductionmentioning
confidence: 99%